Predicting of Komodo dragon's potential prey habitat suitability using MaxEnt in Riung Nature Reserve, Flores, East Nusa Tenggara, Indonesia - FADLAN PRAMATANA; YUSRATUL AINI; NIXON RAMMANG; YOSEP SERAN MAU; I G.B. ADWITA ARSA; ARIEF MAHMUD (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Pramatana F, Aini Y, Rammang N, Mau YS, Arsa IGBA, Mahmud A. 2023. Predicting of Komodo dragon's potential prey habitat suitability using MaxEnt in Riung Nature Reserve, Flores East Nusa Tenggara. Biodiversitas 24: 3128-3139. The Komodo dragon (Varanus komodoensis Ouwens, 1912) is a big lizard species from the Varanidae family that belongs to the Endangered category (EN) listed on the IUCN red list and Appendix I CITES. This study aimed to reveal the distribution of potential preys Komodo dragons in Rinca Island, Komodo National Park, Manggarai District, East Nusa Tenggara, Indonesia, using Maximum Entropy (MaxEnt), which was collected using rapid assessment methods. The presences of the Komodo dragon's potential prey come from direct and indirect observation or previous studies. We collected 510 points of Komodo dragon prey presence in Riung, Ngada District, East Nusa Tenggara, Indonesia from six species, including cattle, but only used 127 points for analysis based on the correlation. Long-tailed macaque, wild boar, civet, Timor deer, feral horses, and cows were the potential prey for komodo in Riung. Most of the points come from cattle, such as cows. On the other hand, we used environmental habitat to represent prey habitats such as elevation, slope, land surface temperature, moisture index, vegetation index, and distance from specific objects such as distance from agriculture, rivers, road, savanna, and settlement. Komodo dragon's potential prey in Riung was distributed in savanna, mangrove, and lowland forest. The result showed three suitable habitats for the Komodo dragon's potential prey dominated by low and moderate-suitability areas.